ANALISIS EFEKTIVITAS PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA MOJOKERTO - APRILLITAWATI, DEBI (Jurnal Akuntansi AKUNESA, 2014)
One source of original revenue in one region is the tax. A parking tax is one kind of tax. The formulation of this problem is how to rate the effectiveness of the parking tax on the original income in Mojokerto in the years of 2009-2013. This research method is using qualitative descriptive method. The results of this study demonstrate the effectiveness of relatively effective parking tax. Realization of the parking tax in 2009 amounted to 104.12%, 2010 saw strong decrease of 91.09%. In 2011 returned decreased by 78.49%, in 2012 an increase of 114.77%. In 2013, it was decreased by 93.05%. Year 2010-2011 due to parking management, they are closed and did not operate in 2013, because the number of motor vehicles parking area was not maximal. Parking management is done in a way to provide good service as provide comfort and confidence.Keywords: Local Revenue, parking tax, Effectiveness.